Strategic improvement planning in schools: A sociotechnical approach for understanding current practices and design recommendations. (October 2019) - Demir, Fatih; Kim, So Mi; Current, Neeley; Jahnke, Isa
The schools in the United States undergo reforms that involve the integration of data-intensive improvement process known as strategic improvement plans (SIPs). This process requires digital systems to set goals, create interventions, use and analyse student data, monitor and report SIPs. A challenge with digital systems is the integration of a highly diverse set of data sources and identifying users who are engaged with the processes. This study explored how teachers and principals carry out SIPs currently. We applied the sociotechnical walkthrough, a qualitative method that combines a modelling notation and focus group interviews to understand the current workflows, technology use and interactions of teachers and principals developing SIPs. The results illustrate a variety of existing activities and indicate how a newly developed technology may have an impact as well as propose design recommendations to fill a gap in managing SIPs.